2022
DOI: 10.1155/2022/6743690
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Inositol Supplementation on Growth, Liver Histology, Lipid Metabolism, and Related Genes Expression on Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed High-Lipid Diets

Abstract: An 8-week feeding trial was conducted to investigate the effects of dietary inositol on growth performance, lipid metabolism, and expression of lipid related genes of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) (initial body weight 6.76 ± 0.34  g). Six isonitrogenous and isolipidic (16.35%) diets were formulated to contain graded levels of inositol (0.17 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
2
2
0
Order By: Relevance
“…Additionally, the WGR, SGR, and FER of largemouth bass feedin a diet supplemented with 250 mg/kg inositol increased significantly. These results were consistent with the study on golden pompano (Trachinotus ovatus) [15], juvenile barramundi (Lates calcarifer Bloch) [25], juvenile tilapia (Oreochromis niloticus × Oreochromis aureus) [26], juvenile Chinese mitten crab (Eriocheir sinensis) [27], and Juvenile hybird grouper (Brown-marbled Grouper Epinephelus fuscoguttatus ♀ × giant grouper E. lanceolatus ♂) [28]. Studies have pointed out that inositol is involved in the synthesis of phosphatidyl inositol, and phosphatidyl inositol could generate inositol triphosphate through phosphorylation, which could regulate the concentration of calcium ions and control the release of acetylcholine.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the WGR, SGR, and FER of largemouth bass feedin a diet supplemented with 250 mg/kg inositol increased significantly. These results were consistent with the study on golden pompano (Trachinotus ovatus) [15], juvenile barramundi (Lates calcarifer Bloch) [25], juvenile tilapia (Oreochromis niloticus × Oreochromis aureus) [26], juvenile Chinese mitten crab (Eriocheir sinensis) [27], and Juvenile hybird grouper (Brown-marbled Grouper Epinephelus fuscoguttatus ♀ × giant grouper E. lanceolatus ♂) [28]. Studies have pointed out that inositol is involved in the synthesis of phosphatidyl inositol, and phosphatidyl inositol could generate inositol triphosphate through phosphorylation, which could regulate the concentration of calcium ions and control the release of acetylcholine.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, paraffin sections of liver were prepared to evaluate the efficacy of protein levels in a high-lipid diet on hepatic histologic changes. Previous studies have shown that the liver could be damaged by high-lipid diets [59] or environmental toxicants manifested by nuclear hypertrophy, karyolysis, indistinguishable cell contours, extensive hepatocellular vacuolation and other phenomena [2,60,61]. Similar symptoms were observed in the control group of this study but the 420 g/kg group reduced the histological abnormalities caused by the high-lipid diet.…”
Section: Discussionsupporting
confidence: 86%
“…This indicates that T-AOC is largely influenced by the activity of these two enzymes. Studies have shown that, when large amounts of oxygen radicals are present in the body [2,41], if the antioxidant capacity of the fish's antioxidant system is weak, it fails to scavenge ROS in time, which in turn causes oxidative damage to cells and promotes lipid peroxidation [42]. In the tissues and organs of the body, the concentration of MDA, the end product of lipid peroxidation, is not only a direct reflection of the antioxidant capacity of the tissues and organs, but also a measure of the antioxidant capacity of the body [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation